2016
DOI: 10.1136/neurintsurg-2015-012220
|View full text |Cite
|
Sign up to set email alerts
|

Weekend effect in endovascular stroke treatment: do treatment decisions, procedural times, and outcome depend on time of admission?

Abstract: It is possible to produce competitive procedural times regardless of the time of admission and to prevent a treatment decision bias when standard operating procedures are applied consistently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…This is consistent with a previous study that suggested the absence of a weekend effect on stroke procedural times 16. However, the present study did suggest a delay of approximately 50 min from notification to puncture during non-work hours compared with work hours.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a previous study that suggested the absence of a weekend effect on stroke procedural times 16. However, the present study did suggest a delay of approximately 50 min from notification to puncture during non-work hours compared with work hours.…”
Section: Discussionsupporting
confidence: 93%
“…These metrics should be applicable regardless of the time of the day and regardless of whether the patient presents on a weekday versus a weekend. 103 These metrics represent maximum recommended times. Because of ample evidence that, the shorter the time to reperfusion, the higher the likelihood of a favorable outcome, all centers should strive to initiate endovascular therapy within the shortest possible time frame.…”
Section: Time Intervalsmentioning
confidence: 99%
“…Two recent studies of in-hours and out-of-hours thrombectomy from the United States [ 20 ] and Germany [ 21 ] reported similar delays in door-to-groin times (21 min and 20 min respectively), but also found worse early [ 21 ] and late [ 20 ] outcomes in patients treated out-of-hours. In contrast, another study from Germany, with no delay in door-to-groin time out-of-hours, found no difference in early or late outcomes following mechanical thrombectomy [ 22 ]. Outcomes were no different in- and out-of-hours in our hospital.…”
Section: Discussionmentioning
confidence: 99%